Transformational Leadership of The Principal in Enhancing Teachers’ Digital Literacy at SMP Negeri 3 Lubuklinggau - Vivi Juniarti; Sudarwan Danim; Muhammad Kristiawan (PPSDP International Journal of Education, 2026)
This study provides an in-depth description of the principal’s role in enhancing teachers’ digital literacy through the application of transformational leadership at SMP Negeri 3 Lubuklinggau. Digital literacy in this research encompasses four aspects: digital competence, digital security, digital culture, and digital ethics. A qualitative case study was employed, with data collected through in-depth interviews, observations, and document analysis. Data were analyzed using reduction, display, and conclusion drawing techniques. The findings indicate that the principal consistently applies the four dimensions of transformational leadership. Idealized influence is reflected in role modeling and integrity; inspirational motivation in moral support, digital-based targets, and recognition; intellectual stimulation in training, innovation, and experimentation; and individualized consideration in tailored guidance. These practices improved teachers’ digital literacy, evidenced by diverse digital media use, increased confidence, and collaborative culture. Challenges remain in disparities of competence and low motivation among senior teachers. Recommendations include continuous training, mentoring, improved facilities, and documentation of best practices.